PATIENT WITH PSORIASIS KEEPING THE USE OF IMMUNOBIOLOGICALS AFTER TWO EPISODES OF PULMONARY TUBERCULOSIS - Silva, Pedro Etienne Arreguy Rodrigues; Marinho, Flávia Estrela Maroja; Nishimori, Fátima Satomi; Mendonça, Camila Nemoto; Avelleira, João Carlos Regazzi (Journal of the Portuguese Society of Dermatology and Venereology, 2013)
The authors report the case of a 58 years old patient, with psoriasis, psoriatic arthritis and Crohn’s di- sease, who developed two episodes of pulmonary tuberculosis during the immunobiological therapy. While treating the second episode of pulmonary tuberculosis, it was decided to reinstate the use of immunobiological, given the severity of the Crohn’s disease and the poor control of psoriasis with other drugs, evolving with good results in controlling the activity of Crohn’s disease, psoriasis and psoriatic arthritis. KEYWORDS – Psoriasis; Mycobacterium tuberculosis; Arthritis, psoriatic; Crohn disease; Immunologic factors.